Tokyo perceptions study infograohic - McNamara, A.; Harris, R.; Minahan, C. (Australian Institute of Sport, 2023)
The aim of the study is to understand what Australian elite female athletes think about the effect of their menstrual cycle on performance. Why? Both general and athletic populations frequently report menstrual symptoms such as pain, fatigue, and heavy bleeding. There is not enough evidence to determine if the menstrual cycle phase or menstrual symptoms affect performance. The next steps are: > Stronger focus on supporting para-athletes and athletes in aesthetic sports given higher numbers of feeling affected. > Raise awareness about menstrual cycle tracking. > Improve education for athletes and role holders around menstrual cycle, > Screen athletes for menstrual cycle related pain. > Encourage more high-quality research in this space.